Assessment of structural nonlinearities employing extremes of dynamic responses. (January 2018) - Pakrashi, Vikram; Fitzgerald, Paul; O'Leary, Michael; Jaksic, Vesna; Ryan, Kevin; Basu, Biswajit
A range of methodologies exist for estimating nonlinear responses of structural systems using numerical simulations. However, efforts in relation to experimental methods in this regard still warrant further investigation. This paper presents an approach for assessing structural nonlinearities using the extremes of dynamic responses of the structural system under consideration. The approach allows revisiting and parameter tuning of theoretical models of structures based on experimental studies. A single degree of freedom system was excited in this study using broadband input excitations and the output dynamic responses were measured using different devices. The type and extent of experimentation required for implementation of the presented technique was investigated along with the effects of the estimates of the measured variables and the effects related to different measurement devices.